2015
DOI: 10.3389/fimmu.2015.00233
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of NKT-Cell Responses to Chlamydial Infection

Abstract: Natural killer T (NKT) cells have gained great attention owing to their critical functional roles in immunity to various pathogens. In this review, we provide an overview of the current knowledge on the role of NKT cells in host defense against and pathogenesis due to Chlamydia, which is an intracellular bacterial pathogen that poses a threat to the public health worldwide. Accumulating evidence has demonstrated that NKT cells, particularly invariant NKT (iNKT) cells, play a crucial role in host defense agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Perhaps even more intriguing, i NKT cell activation could have seemingly contradictory consequences during infection with different species of the same pathogen (e.g., Chlamydia spp.) ( 37 ). CD1d −/− and Jα18 −/− mice have been used extensively to address the contributions of i NKT cells in infection and immunity.…”
mentioning
confidence: 99%
“…Perhaps even more intriguing, i NKT cell activation could have seemingly contradictory consequences during infection with different species of the same pathogen (e.g., Chlamydia spp.) ( 37 ). CD1d −/− and Jα18 −/− mice have been used extensively to address the contributions of i NKT cells in infection and immunity.…”
mentioning
confidence: 99%
“…Activated type I NKT can promote the maturation and differentiation of DCs into CD8+/CD103+ DCs, which can further activate T cell differentiation into functional Th1 or Tc1-like peptide antigen-specific T cells. Activated antigen-specific CD4 + Th1 and CD8 + Tc1 can suppress bacterial infection ( 93 , 94 ). However, CD1d-restricted NKT cells can regulate the immune response to chlamydial infection and cause immunopathological damage.…”
Section: Evasion Of Innate-like Lymphocytes [Ills]mentioning
confidence: 99%
“…It was reported that these bacteria abundantly express glycosphingolipids (GSLs) which have high similarity in structures to a-GalCer. Our group studied the role of NKT cells in host defense against Chlamydiae, an intracellular bacterial pathogen that poses a threat to public health worldwide (29,30). We found that chlamydial glycolipid exoantigen (GLXA), a glycolipid antigen derived from Chlamydia muridarum, can activate iNKT cells at in vitro and in vivo settings.…”
Section: The Activation Of Nkt Cells and The Role Of Dcsmentioning
confidence: 99%